Micro-grid transient and steady state operation control method and device, terminal equipment and storage medium - PANG XUEYUE; GU YICAN; ZHANG XINGZI; LIU HAOYI; SHEN YANKUN; YANG HAISEN; YAO JINMING; SUN HAO; LIU YIMING; XU QIN; QIU GUOBIN; ZHANG SHIPENG; et al. (2023)
The invention discloses a micro-grid transient and steady state operation control method and device, terminal equipment and a storage medium. The method comprises the following steps: monitoring the load rate of each diesel generator in a micro-grid and the energy storage SOC state value of an energy storage system in real time; when the load rate of any diesel generator is higher than the operation upper limit and the energy storage SOC is within the preset range, the output power of the energy storage system is improved; when the load rate of any diesel generator is higher than the operation upper limit and the energy storage SOC is not smaller than the energy storage operation upper limit, interruptible loads are cut off; when the load rate of any diesel generator is lower than the operation lower limit and the energy storage SOC is within the preset range, the output power of the energy storage system is reduced; and when the load rate of any diesel generator is lower than the operation lower limit and th